2010
DOI: 10.1249/mss.0b013e3181d964e4
|View full text |Cite
|
Sign up to set email alerts
|

Early Time Course of Akt Phosphorylation after Endurance and Resistance Exercise

Abstract: We show a similar time course for Akt-mTOR-S6K phosphorylation during the initial 60-min recovery period after divergent contractile stimuli. Conversely, enhanced phosphorylation status of proteins that promote glucose transport and glycogen synthesis only occurred after endurance exercise. Our results indicate that endurance and resistance exercise initiate translational signaling, but high-load, low-repetition contractile activity failed to promote phosphorylation of pathways regulating glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
109
5
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(126 citation statements)
references
References 37 publications
9
109
5
3
Order By: Relevance
“…The noted increase in ERK 1/2 phosphorylation is consistent with our previous report, which suggests that harvesting multiple biopsy samples from one incision site may elicit an inflammatory response that might influence intracellular signaling (13). Changes in Akt, mTOR, rpS6, and eEF2 phosphorylation are similar to those in other studies and are consistent with an upregulation of mRNA translation initiation, elongation, and increased MPS after exercise (1,15,16,(47)(48)(49). It is important to note that we were unable to detect significant differences in the phosphorylation of any critical mTORC1 intracellular signaling protein between the dietary treatment groups, despite the differences observed in MPS.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The noted increase in ERK 1/2 phosphorylation is consistent with our previous report, which suggests that harvesting multiple biopsy samples from one incision site may elicit an inflammatory response that might influence intracellular signaling (13). Changes in Akt, mTOR, rpS6, and eEF2 phosphorylation are similar to those in other studies and are consistent with an upregulation of mRNA translation initiation, elongation, and increased MPS after exercise (1,15,16,(47)(48)(49). It is important to note that we were unable to detect significant differences in the phosphorylation of any critical mTORC1 intracellular signaling protein between the dietary treatment groups, despite the differences observed in MPS.…”
Section: Discussionsupporting
confidence: 90%
“…The discrepant observations regarding the influence of endurance-type exercise and feeding on mTORC1 intracellular signaling may be attributed to between-study differences in exercise intensity and duration, in the training state of the study volunteers, and in the timing of the muscle biopsy collections during recovery (48,(50)(51)(52). In the current study, moderate steady state exercise coupled with EAA supplementation increased Akt, mTOR, rpS6, and ERK 1/2 and reduced eEF2 phosphorylation.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…It should be noted that in the current study, a significant but temporal increase in mTORC1 activity was observed in response to EE alone. Immediate mTORC1 signaling response is not RE specific, and EE also activates mTORC1 signaling (7,18). In the present study, EE also increased phosphorylation of Akt, an upstream stimulator of mTORC1.…”
Section: Discussionsupporting
confidence: 48%
“…This is unsurprising given the necessity to initiate and increase gene translation and protein expression responses that ultimately form the basis of adaptation and muscle remodelling to exercise (Camera et al, 2010). Increases in mTOR, rpS6 and 4E-BP1 phosphorylation have been reported when protein was ingested following endurance exercise compared with a carbohydrate-fat beverage (Rowlands et al, 2015) or a nonenergetic placebo (Ivy et al, 2008).…”
Section: Reduced Energy Availabilitymentioning
confidence: 99%